2011
DOI: 10.1523/jneurosci.2737-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Specific Changes in Resting-State Sensorimotor Networks after Motor Learning

Abstract: Motor learning changes the activity of cortical motor and subcortical areas of the brain, but does learning affect sensory systems as well? We examined in humans the effects of motor learning using fMRI measures of functional connectivity under resting conditions, and found persistent changes in networks involving both motor and somatosensory areas of the brain. We developed a technique that allows us to distinguish changes in functional connectivity that can be attributed to motor learning from those that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

31
225
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 242 publications
(264 citation statements)
references
References 45 publications
31
225
0
Order By: Relevance
“…Thus, in effect, the functional role of the observed sensory change is that, in combination with motor learning, the two act together to keep motor and sensory systems in register. The present findings complement the results of recent studies in which we have used fMRI under resting-state conditions to assess changes that occur in association with motor learning in the functional connectivity between the brain's sensory and motor regions (Vahdat et al 2011). In that work, it was observed that changes in brain networks that occur in conjunction with learning can be partitioned into those that are primarily motor in nature and those that reflect the perceptual changes that occur in combination with motor learning.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Thus, in effect, the functional role of the observed sensory change is that, in combination with motor learning, the two act together to keep motor and sensory systems in register. The present findings complement the results of recent studies in which we have used fMRI under resting-state conditions to assess changes that occur in association with motor learning in the functional connectivity between the brain's sensory and motor regions (Vahdat et al 2011). In that work, it was observed that changes in brain networks that occur in conjunction with learning can be partitioned into those that are primarily motor in nature and those that reflect the perceptual changes that occur in combination with motor learning.…”
Section: Discussionsupporting
confidence: 84%
“…The SEP changes observed in the present study follow the same pattern as psychophysical measures of perceptual change (Ostry et al 2010, Vahdat et al 2011. Both SEP magnitudes and measures of sensed limb position vary with the extent of learning, and neither is observed to change in the context of passive movement that does not involve learning.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations